Pediatric cases caused by Streptococcus pneumoniae Serotype 3 - Aslinur Ozkaya-Parlakay; Meltem Polat; Belgin Gulhan; Saliha Kanik-Yuksek; Hasan Tezer; Selin Nar-Otgun (Taylor & Francis Group, 2019)
Streptococcus pneumoniae causes invasive pneumococcal disease (IPD), leading to high morbidity and mortality worldwide. Although nonvaccine serotypes constitute a major issue in the aspect of invasive pneumococcal disease, serotypes included in PCV13 still continue to be a problem. Vaccination with very high coverage and multicenter surveillance studies would be beneficial to decrease carriage of vaccine and nonvaccine serotypes of pneumococcus and monitor changing seroepidemiology.